Kajian Ekonomi Kualitas Pangan: Upaya Mendukung Ketahanan Pangan Berkelanjutan di Pedesaan Provinsi DIY - Soeroso, Amiluhur; Susilo, Y. Sri (UI Scholars Hub, 2009)
This research aims to explore quantified of monetary use value of food quality in the context of food security. Data were obtained from interviews towards 561 people of rural area in regency of Sleman, Bantul, Kulon Progo and Gunungkidul which are all in Yogyakarta Special Province or Daerah Istimewa Yogyakarta (DIY). This research uses close-ended contingent valuation method (CVM). The result points out that the public willingness to pay for better food quality is high. Thus, the public loss which is caused by poor management of food security policy will be very high in financial term.